Perspectives of cell therapy for myocardial infarction and heart failure based on cardiosphere cells - K. V. Dergilev; Iu. D. Vasilets; Z. I. Tsokolaeva; E. S. Zubkova; E. V. Parfenova (Терапевтический архив, 2020)
Cardiovascular diseases are the leading cause of morbidity and mortality worldwide. In recent years, researchers are attracted to the use of cell therapy based on stem cell and progenitor cells, which has been a promising strategy for cardiac repair after injury. However, conducted research using intracoronary or intramyocardial transplantation of various types of stem/progenitor cells as a cell suspension showed modest efficiency. This is due to the low degree of integration and cell survival after transplantation. To overcome these limitations, the concept of the use of multicellular spheroids modeling the natural microenvironment of cells has been proposed, which allows maintaining their viability and therapeutic properties. It is of great interest to use so-called cardial spheroids (cardiospheres) spontaneously forming three-dimensional structures under low-adhesive conditions, consisting of a heterogeneous population of myocardial progenitor cells and extracellular matrix proteins. This review presents data on methods for creating cardiospheres, directed regulation of their properties and reparative potential, as well as the results of preclinical and clinical studies on their use for the treatment of heart diseases.